Is it what you inherited or what you learnt? Intergenerational linkage and interpersonal inequality in Senegal - Sylvie Lambert; Martin Ravallion; Dominique Van de Walle (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2011)
Using original survey data on Senegal that include an individualized measure of consumption, we study the role played by land inheritance, other bequests and parental background as influences on an adult's economic welfare and economic activities. While intergenerational linkages are evident, we find a seemingly high degree of mobility across generations, associated with the shift from farm to non-farm sectors and the greater economic activity of women. Male-dominated bequests of land and housing bring little gain to mean consumption and play little role in explaining inequality. Inheritance of non-land assets and the education and occupation of parents (especially the mother) and their choices about children's schooling are more important to adult welfare than property inheritance. Significant gender inequality in consumption is evident.
Keywords: D31; I31; O15; 330; inheritance; land; mobility; inequality; gender; Erbe; Generationenbeziehungen; Intertemporale Einkommensverteilung; Intergenerational Mobility; Senegal